Why have child pedestrian death rates fallen? - Roberts, I (1993)
Pedestrian injuries are a leading cause of childhood mortality and disability. Over the past two decades in Britain child pedestrian death rates have fallen despite large increases in traffic volume. In this paper Roberts examines the likely reasons for this decline. He argues that neither prevention programmes nor improvements in medical care are a plausible explanation and that the decline is most likely the result of a substantial reduction in children's traffic exposure. He believes, however, that restricting children's traffic exposure exacerbates socioeconomic differentials in childhood mortality and denies children their right to mobility. Roberts is convinced that one answer is for British transport policy to be aimed at providing mobility equitably rather than struggling to meet the ever increasing demands of car travel.